Strategi Pembinaan dan Pendampingan Koperasi Peternak Sapi Perah Dalam Mendukung Keberlangsungan Koperasi Dan Ketahanan Ekonomi Anggota (Studi di KUD Sinar Jaya) - Apriwandi Apriwandi (STKIP PGRI SITUBONDO, 2021)
The purpose of this study to examine the use of mentoring and coaching strategies in dairy farmer cooperatives as a means of improving cooperative performance. at this time, cooperatives must survive and maintain the success of their organizations at the highest level because of the high expectations of cooperative stakeholders. Taking place in such a fierce competitive environment requires a more effective and efficient attitude through increasing the capability of the cooperative management staff. Coaching and mentoring can be the key to success for cooperative organizations in maintaining the competitiveness and management power of cooperatives. The research findings show that the problems in cooperative management and accounting have not been achieved as their best. Most of the accounting staff do not understand the accounting process and in the end the financial reports are not sufficient to meet the needs of cooperative users. This research focuses on assisting the accounting process and cooperative management as a support activity for cooperative activities, which will be a source of motivation and an effective performance booster not only for cooperatives but also for management and staff.